An Ethical Reflection on the Heritability Argument in the Germline Genetic Intervention Debate - Barış, Maide (International Journal of Human and Health Sciences (IJHHS), 2021)
Germline genetic intervention (GGI) has been one of the most discussed topics within the bioethics literature since 2012, when the programming of CRISPR/Cas9 for a specifically targeted gene region has become possible. While some authors are optimistic about what GGI may offer, others strongly disagree and refute the use of this technology for different reasons. This paper will aim to examine one of the most widespread arguments against GGI, namely “heritability” argument, comprehensively. Firstly, it will aim to examine the moral importance of the germline. Secondly, it will try to understand three possible assumptions of the heritability argument. Then it will try to respond to these assumptions and argue that they are neither scientifically supportable nor rationally solid for rejecting GGI altogether. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 405-411